Entrepreneurial Orientation and SMEs Business Peformance: The Role of Technology and Competitive Intensity as Mediating - Nofirda, Fitri Ayu; Azhari, Intan Putri (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. The purpose of this study is to analyze the influence of entrepreneurial orientation including innovation, proactiveness and courage in taking risks in Pekanbaru City, Riau Province Indonesia. SMEs contributes largely to Indonesia's economy. However, these enterprises often struggle with limited resources leading to weaker performance. The research problem centers on identifying factors that can enhance the BP, mainly through Technology and CI. This study uses quantitative and descriptive research methods using SEM - AMOS 26. Data is collected using online survey. The research sample is a portion of the leaders or owners of SMEs in the songket business commodity using a non-probability delivery method, namely a purposive sampling. Sample of the study was 240 respondents. Conceptually, this study found interesting relationship between innovation, proactive, risk taking, technology, competitive intensity and business perfomance then called as entrepreneurial orientation. The empirical results reveal that technology and competitive intensity significantly mediate the relationship between EO and SME performance. Therefore, with new findings, the study extends the literature on serial mediation in the EO-performance of SMEs. This study has important implications for SMEs that are seeking to gain a competitive advantage. The findings offer an additional insight to managers on entrepreneurial orientation strategy to increase business performance. Keywords: Business Performance, Entrepreneurial Orientation, Innovation, SMEs